At-home disposal practices of used insulin needles among patients with diabetes in China: A single-center, cross-sectional study - Tu, Haixia; Lu, Xueqin; Wang, Jialu; Sheng, Zhiqiong; Liu, Danman; Li, Jufang; Sun, Caixia; Yin, Zhiqin (Frontiers in Public Health, 2022)
Background: Most insulin injections for people with diabetes are administered at home, thus generating many used needles. Unsafe disposal of these at-home needles can lead to needle stick injuries, blood-borne disease transmission, and environmental contamination. Previous studies have shown varying results on the prevalence of and factors associated with safe sharps disposal practices of people with diabetes. Objective: To assess the prevalence of and the factors associated with the safe disposal of used insulin needles among patients with diabetes. Methods: We collected data from 271 insulin-using patients at a tertiary care hospital in China. A self-designed instrument was used to assess sociodemographic data, disease- and treatment-related characteristics, sharps disposal practices, education on diabetes self-management and sharps disposal, and awareness of the potential risks associated with unsafe sharps disposal. Multivariate logistic regression analysis was used to explore factors associated with safe sharps disposal practices. Results: Only 10.3% (28/271) of participants disposed of used at-home insulin needles in a safe manner, and 14.8% (45/271) of participants had received previous instruction on sharps disposal. Previous sharps disposal instruction (AOR=4.143, 95% CI=1.642–10.450) and awareness of the risk of blood-borne pathogen transmission (AOR=3.064, 95% CI=1.332–7.046) were associated with safe disposal of used insulin needles. Conclusion: In our study, the prevalence of safe sharps disposal practices was low, and a minority of respondents had received previous instruction on sharps disposal. Participants who had previously received instruction and were aware of the risk of blood-borne pathogen transmission were more likely to handle sharps safely. Our study findings suggest that health care professionals should pay attention to sharps disposal practices of patients with diabetes and conduct diabetes education programs that include information on safe sharps disposal methods and potential hazards of unsafe sharps disposal.